2019
DOI: 10.3390/su11071910
|View full text |Cite
|
Sign up to set email alerts
|

Examining German Media Coverage of the Re-Evaluation of Glyphosate

Abstract: This study investigates media coverage of the re-evaluation process of glyphosate from 1 January 2015 to 31 March 2018. In a comparative, qualitative print media analysis, the promotion of claims and the use of narratives of Die Zeit, a weekly newspaper, and top agrar, an agricultural trade journal, are explored. Results identify noticeable differences in both media outlets’ news reporting. Whereas Die Zeit focused on potential health risks and the scientific controversy, top agrar’s coverage emphasized the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 62 publications
0
4
0
2
Order By: Relevance
“…Robinson 2001 ). Daily newspapers publish more news than weekly magazines while weeklies offer more in-depth information and comments (Villnow et al 2019 ). The two daily newspapers FAZ and SZ cover, besides national and international news, topics of the federated states Hesse respectively Bavaria they are situated in.…”
Section: Methodsmentioning
confidence: 99%
“…Robinson 2001 ). Daily newspapers publish more news than weekly magazines while weeklies offer more in-depth information and comments (Villnow et al 2019 ). The two daily newspapers FAZ and SZ cover, besides national and international news, topics of the federated states Hesse respectively Bavaria they are situated in.…”
Section: Methodsmentioning
confidence: 99%
“…This is in contrast with determinations by the USEPA (USEPA, 2016), the European Food Safety Authority (EFSA, 2015), and the WHO's Joint Meetings on Pesticide Residues (WHO, 2016), among others, which concluded that glyphosate is unlikely to pose carcinogenic risks to humans. These discrepancies sparked heated debates among stakeholders and in the media (Lock, 2020; Villnow et al, 2019), and contributed to controversial regulatory decisions in several countries, most notably within the European Union (Székács & Darvas, 2018; Tarazona et al, 2017). Within the European Union, the case is further complicated by the fact that active ingredients (i.e., glyphosate) are regulated at European Union level whereas the formulated products (e.g., Roundup® pesticide) are regulated at member state level (Székács & Darvas, 2018).…”
Section: The Importance Of Scientific Research and Addressing Attacks...mentioning
confidence: 99%
“…Research has shown that agricultural involvement in such social debates can be reactive rather than proactive, with communication often coming after a 'hot topic' farming practice has already become the centre of contentious conversation, thus the tone can come across as defensive rather than engaging [13]. However, social media has also presented opportunities to the farming community: traditionally, third party gatekeepers (e.g., retailers, journalists) have dominated public messaging on agricultural issues, often bringing their own particular framing biases [14]. In contrast, social media platforms have fostered the development of a new era of farmers empowered to take public communication into their own hands and speak directly to the consumer-citizen [11].…”
Section: Farmer-citizen Engagementmentioning
confidence: 99%